PRODUKSI PROTEASE ALKALI DAN KERATINASE DARI Brevibacillus agri A-03 TERMOFILIK - Agustien, Anthoni; Nurhajati, Jetty; Udin, Linar Z.; Aditiawati, Pingkan (Universitas Andalas, 2010)
ABSTRAK Protease alkaline and keratinase are a group of protease enzym which have important value in detergen industry and skin tannery. Brevibacillus agri A-03 is thermophilic bacteria isolate that comes from Ambayan Sumatera Barat hot spring and has the ability to produce protease and keratinase. The purpose of this research is to get protease alkaline and thermostable keratinase from Brevibacilus agri-A03. thermostable enzym is produced from enzym production enzym that contains kasein and keratin at various medium pH, inoculum incubation temperature and medium type. Enzym activity is measured by modified Walker methode, protein content is measured by Lowry methode. Protease alkaline is produced at exponential phase, maximum at 18th hours of incubation and keratinase is produced at stationer phase, maximum at 22nd hours. Both enzym is produced optimically at medium pH condition 9.0; incubation temperature 55°C, inoculum 5% by using modified Johnvesly and Naik medium with each protease and keratinase specific activity 1.927 and 1.047 U/mg Keywords: Protease alkaline, Keratinase, Thermofilic, Brevibacillus agri A-03